The Quest for Systemic Islamic Economic Studies from Interdisciplinary Perspectives - Zainal Abidin (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2022)
The method in Islamic studies is a necessity for the reason that with a correct and accurate method, Islamic study becomes an interesting exploration in the academia. In Islamic Studies courses, issues of life problems associated with Islam need to be handled. This paper discerns the challenges and opportunities that arise in Islamic studies and relate these to the development of the Islamic economic realm. This article argues that Islamic studies is faced with a huge prospect , namely a reform at the philosophical level. Hence, concepts to enrich the perspectives using a multi-dimensional approach are suggested. Besides, strengthening the field of text supplementation by presenting an understanding of hermeneutics and understanding the concept of maqasid shari'a are also encouraged. It concludes with an obsession to present a sensitive and integrated Islam with modernity.